Agammaglobulinaemia despite terminal B‐cell differentiation in a patient with a novel LRBA mutation. Issue 5 (26th May 2017) - Al Sukaiti, Nashat; AbdelRahman, Khwater; AlShekaili, Jalila; Al Oraimi, Sumaya; Al Sinani, Aisha; Al Rahbi, Nasser; Cho, Vicky; Field, Matt; Cook, Matthew C
Abstract : Mutations in lipopolysaccharide‐responsive vesicle trafficking, beach and anchor‐containing protein (LRBA) cause immune deficiency and inflammation. Here, we are reporting a novel homozygous mutation in LRBA allele in 7‐year‐old Omani boy, born to consanguineous parents. He presented with type 1 diabetes, autoimmune haematological cytopenia, recurrent chest infections and lymphocytic interstitial lung disease. The patient was treated with CTLA4‐Ig (abatacept) with good outcome every 2 weeks for a period of 3 months. He developed complete IgG deficiency, but remarkably, histological examination revealed germinal centres and plasma cells in lymphoid and inflamed lung tissue. Further charatecterisation showed these cells to express IgM but not IgG. This ex vivo analysis suggests that LRBA mutation confers a defect in class switching despite plasma cell formation.